Development of Speech Assistant Tool for Enhancing University Students’ Oral Presentation Proficiency: A Needs Analysis - Anuar, Nadia; Ahmad Kamil, Maisarah; Md. Ngadiran, Nurizah; Shidrah Mat Daud, Nor (International Journal of English Language Education, 2023)
Oral presentation skills are a highly valued core competency that pre-employment students and graduates should acquire prior to entering the competitive employment sector. However, studies and reports have demonstrated a widening gap between graduates’ proficiency in oral presentations and the industry’s demands. Graduates’ oral presentation performance was reported to be unsatisfactory and workplace presentations are viewed as intimidating by many graduates. These issues necessitate a needs analysis to develop a Speech Assistant Tool (SAT) that can assist students in improving their oral presentation skills. A descriptive research design and a cross-sectional survey research were utilised. A questionnaire consisting of four (4) sections was used to analyse the students’ needs. The questionnaire was distributed via Google Forms to randomly-selected students from two public universities in Malaysia. A total of 179 responses were attained and were subjected to data cleaning, which revealed a total of 147 usable responses. A descriptive analysis was conducted to understand the students’ views on all language skills and their current proficiency in technological skills. A t-test was conducted to examine if there is a significant difference in the needed oral presentation skills, concepts, and learning strategies for the development of SAT between male and female students. The t-test results reported no significant difference between the male and female students. The findings, therefore, proved that students from different universities are experiencing similar issues in oral presentations which necessitate the SAT.